The art of glacier grafting: innovative water harvesting techniques in Ladakh - Shaheen, F.A. (International Water Management Institute, 2016)
As a cold desert with extreme climate and limited precipitaon, Ladakh struggles to meet its irrigaon requirements. In recent years, a historical pracce of graing glaciers and a new innovave technique of building 'ice stupa' has helped communies improve irrigaon access and extend the crop calendar. This Highlight looks at how combining sound science with credible local knowledge is helping people improve climate resilience.